Analytically Modeling of In VitroCalcium Dissolution of Plasma-Sprayed Hydroxyapatite Coatings: Calcium dissolution of hydroxyapatite coatings - Zahra Mohammadi,; Aliakbar Ziaei-Moayyed,; Abdorreza Sheikh-Mehdi Mesgar,; Mohammad Hossain Afdjei, (Iranian Journal of Pharmaceutical Sciences, 2008)
The in vitrodissolution of plasma-sprayed hydroxyapatite (PHA) coatings with different characteristics, produced by various spraying conditions, in a Tris-buffered solution at pH 7.4 was experimentally studied through the measurement of calcium ions release with Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), and then modeled. Three coating characteristics, the crystallinity, the degree of recrystallization and the porosity were evaluated. The analytical modeling revealed that the calcium dissolution process was composed of two stages. The first stage was found to be both surface and diffusion controlled. The second stage was an exactly diffusion controlled dissolution. In the first stage, the solubility and dissolution rate of the PHAcoatings were mainly increased with decreasing the crystallinity, and partly with increasing the degree of recrystallization and the porosity. The degree of recrystallization was found to control the dissolution rate of the PHAcoatings in the second stage. It was suggested that the promotion of a rapid integration of implant to bone can be achieved by the optimization of the degree of crystallinity and recrystallization at coating surface.